Perivascular spaces and basilar artery remodeling in Fabry disease—a dual vascular pathology - Roh, Jieun; Cheon, Chong Kun; Lee, Soo-Yong; Baik, Seung-Kug; Park, Min-Gyu; Park, Kyung-Pil; Ahn, Sung-Ho (Frontiers in Neurology, 2025)
BackgroundFabry disease (FD) is a lysosomal storage disorder that causes glycosphingolipid deposition in the vascular endothelium. Early neurovascular involvement is difficult to detect because conventional magnetic resonance imaging (MRI) findings overlap with age-related small- and large-vessel changes. We hypothesized that integrating microvascular and macrovascular MRI markers could improve the detection of FD-related vasculopathy.MethodsIn a prospective case–control study, 26 genetically confirmed FD patients and 26 age- and sex-matched healthy controls underwent three-Tesla MRI (3 T MRI), including high-resolution vessel wall imaging. The macrovascular metrics included the basilar artery (BA) diameter, BA tortuosity index (BATI), and a composite BA degeneration index (BADI). The microvascular markers included the perivascular space (PVS) burden (Potter scale), white matter lesion severity (modified Fazekas scale), and global cerebral atrophy. Associations with FD were assessed using multivariable logistic regression, adjusting for age, sex, and vascular risk factors. Correlations between microvascular and macrovascular markers and age-stratified analyses were also performed.ResultsPatients with FD exhibited a larger BA diameter, higher PVS burden in the basal ganglia and centrum semiovale, and greater cerebral atrophy than controls, while Fazekas scores were similar. Both PVS burden and BA diameter were independently associated with FD after adjustment, and the PVS burden remained significant after controlling for vascular risk factors. In patients with FD, but not in controls, the PVS burden correlated positively with the BADI, indicating coupled microvascular and macrovascular remodeling. Age-stratified analyses revealed steeper increases in BA metrics and PVS burden with advancing age in patients with FD, suggesting accelerated vascular degeneration.ConclusionCombining the PVS burden with posterior circulation remodeling indices (BA diameter/BADI) reveals the disease-specific coupling of microvascular and macrovascular degeneration in FD. This quantitative MRI approach may enable earlier diagnosis, more precise risk stratification, and monitoring of therapeutic responses in clinical practice.